Digitalization in logistics for textiles – possible fields of application for the Blockchain technology - Natalie Fohrer; Andreas Gade; Markus Muschkiet (Communications in Development and Assembling of Textile Products)
The globalized supply chains of textiles and clothes involve multiple parties from different countries. Flows of goods, information and finances are coordinated through logistic processes, but offer potential for optimization in terms of digitalization and transparency. Incidents of the past prove that fundamental human rights standards and occupational safety are not met in global production countries yet. Legal regulations like the Act on Corporate Due Diligence Obligations for the Prevention of Human Rights Violations in Supply Chains (LkSG) shall help to improve the situation since 2023. Especially small and medium sized enterprises (SME) in Germany, to which the law applies indirectly through private-sector contracts from their non-SME consignees, struggle to control their global supply chain, to provide all necessary data and to ensure a traceable, fraud-resistant and manageable flow of information. Hence, the Center Textile Logistics investigated the potential of the Blockchain technology and its application possibilities for textile supply chains. The Blockchain technology offer chances in terms of securing clothing trademarks, proofing that standards of seals and certificates are met, proofing that political and legal regulations are met and in terms of controlling global processes that involve international suppliers and partners. However, the current state of the art of digitalization is often too low to directly apply the Blockchain technology and has to be improved first. The cost-benefit ratio has to be evaluated individually but the Blockchain technology offers great potential to rise transparency, ease communication and critical data exchange along textile supply chains.